Substantiation of the intensified dump reclamation in the process of field development - Kalybekov, Tursun; Rysbekov, Kanay; Sandibekov, Мanarbek; Bi, Yin Li; Toktarov, Ayan (National Mining University, 2020)
Purpose is to substantiate intensification of dozer dump reclamation in the process of open pit-mining. Methods. Analysis of methods intended to intensify reclamation activities in the context of open-pit mineral extraction under different mining and geological conditions has been applied. Innovative operation schedule of dump reclamation has been developed on the basis of critical analysis and proper analytical research. Findings. Operation schedule to form a dozer dump has been substantiated taking into consideration rock suitability for reclamation making it possible to mitigate impact of mining on the environment. Algorithm to calculate dozer dump parameters has been developed as well as a digital topographic model of selective dump formation. Originality. The developed operation schedule for selective formation of the external dump differs from the available one in the simultaneous layer dumping to intensify surface of its dumped share in the process of open-pit mining. Practical implications. Use of the method of selective surface formation in terms of a dozer dump, taking into consideration overburden suitability for reclamation, helps intensify reclamation of the soils disturbed during field development.

Мета. Обґрунтування можливості інтенсифікації рекультивації поверхонь бульдозерних відвалів при відкритій розробці родовищ. Методика. Застосовано аналіз способів інтенсифікації рекультиваційних робіт при відкритому видобутку корисних копалин у різних гірничо-геологічних умовах. На підставі критичного аналізу і власних аналітичних досліджень розроблена нова технологічна схема рекультивації відвалу. Результати. Обґрунтовано технологічну схема формування бульдозерного відвалу з урахуванням придатності порід для цілей рекультивації, що дозволяє знизити негативний вплив гірничих робіт на навколишнє середовище. Розроблено алгоритм розрахунку параметрів бульдозерних відвалів і створена цифрова топографічна модель селективного формування відвалу. Наукова новизна. Розроблена нова технологічна схема селективного формування зовнішнього бульдозерного відвалу відрізняється від існуючих одночасним відсипанням відвальних ярусів для інтенсифікації рекультивації поверхні його відсипаної частини в період експлуатації родовища відкритим способом. Практична значимість. Застосування технології селективного формування поверхні на прикладі бульдозерного відвалу з урахуванням придатності розкривних порід для рекультивації дає можливість інтенсифікувати рекультивацію порушених земель у процесі експлуатації родовищ.

Цель. Обоснование возможности интенсификации рекультивации поверхностей бульдозерных отвалов при открытой разработке месторождений. Методика. Применен анализ способов интенсификации рекультивационных работ при открытой добыче полезных ископаемых в различных горно-геологических условиях. На основании критического анализа и собственных аналитических исследований разработана новая технологическая схема рекультивации отвала. Результаты. Обоснована технологическая схема формирования бульдозерного отвала с учетом пригодности пород для целей рекультивации, позволяющая снизить отрицательное влияние горных работ на окружающую среду. Разработан алгоритм расчета параметров бульдозерных отвалов и создана цифровая топографическая модель селективного формирования отвала. Научная новизна. Разработанная новая технологическая схема селективного формирования внешнего бульдозерного отвала отличается от существующих одновременной отсыпкой отвальных ярусов для интенсификации рекультивации поверхности его отсыпанной части в период эксплуатации месторождения открытым способом. Практическая значимость. Применение технологии селективного формирования поверхности на примере бульдозерного отвала с учетом пригодности вскрышных пород для рекультивации дает возможность интенсифицировать рекультивацию нарушенных земель в процессе эксплуатации месторождений.
Keywords: soil disturbance; overburden; open-pit mining; reclamation; dump; rock